2021
DOI: 10.9767/bcrec.16.1.9442.22-30
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Metal Loading Amount on Ni/Mesoporous Silica Extracted from Lapindo Mud Templated by CTAB for Conversion of Waste Cooking Oil into Biofuel

Abstract: The synthesis and characterization of Ni/mesoporous silica (Ni/MS) catalysts from Lapindo mud with various metal loading for the hydrocracking of waste cooking oil into biofuel has been conducted. The MS was synthesized by the hydrothermal method using CTAB as a template. The nickel-metal of 4, 6, and 8 wt% was loaded into the MS using salt precursors of Ni(NO3)2.6H2O via wet impregnation, produced the Ni(4)/MS, Ni(6)/MS, and Ni(8)/MS catalysts, respectively. The materials produced were then characterized by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…13,14 Especially, biogasoline (gasoline-range bio-hydrocarbon) is of great significance due to its high energy density, low viscosity, high stability, shorter ignition delay, and low-pollutant combustion. [15][16][17][18] However, the production of bio-hydrocarbons mainly relies on the hydrodeoxygenation process or thermal cracking of triglycerides (from vegetable oils, animal fats, algae, or other different feedstocks) at temperatures ranging from 250 °C to 450 °C and hydrogen pressure between 10 and 300 bar, [19][20][21][22][23][24] which contradicts the concept of green chemistry advocated now. 25,26 Therefore, finding alternative ways of converting renewable triglycerides into bio-hydrocarbons, especially biogasoline, is highly soughtafter.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Especially, biogasoline (gasoline-range bio-hydrocarbon) is of great significance due to its high energy density, low viscosity, high stability, shorter ignition delay, and low-pollutant combustion. [15][16][17][18] However, the production of bio-hydrocarbons mainly relies on the hydrodeoxygenation process or thermal cracking of triglycerides (from vegetable oils, animal fats, algae, or other different feedstocks) at temperatures ranging from 250 °C to 450 °C and hydrogen pressure between 10 and 300 bar, [19][20][21][22][23][24] which contradicts the concept of green chemistry advocated now. 25,26 Therefore, finding alternative ways of converting renewable triglycerides into bio-hydrocarbons, especially biogasoline, is highly soughtafter.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicate that a high nickel content can reduce the surface area and pore volume of the silica support but does not affect the mesoporous structure. Paramesti et al [11] have successfully tested the activity and selectivity of the Ni/MS catalyst against hydrocracking of waste cooking oil (WCO) into hydrocarbon compounds with variations in Ni concentration of 4%, 6%, and 8% (w/w). The results showed that the catalyst activity of Ni(4)/MS reached 80.57 wt.% and was more selective towards the formation of C5-C12 chain hydrocarbon compounds of 54.22 wt.%.…”
Section: ■ Introductionmentioning
confidence: 99%